Thyroid disorders in women with abnormal uterine bleeding: a tertiary hospital based cross sectional study from Puducherry, India - Ezhil, Rini; K., Nivedita; N., Fatima Shanthini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The most common complaint with which women present for gynecological consultation is abnormal uterine bleeding which may be due to varied etiology. Among non-structural causes for AUB, endocrinological disorders like thyroid dysfunction is very common. Thyroid dysfunction is often overlooked, and unnecessary hormonal or surgical interventions are performed in patients with AUB. Methods: This is a hospital based cross sectional study carried out in Sri Manakula Vinayagar Medical College and Hospital, Puducherry between January 2017 to June 2017 for a period of 6 months and the participants were 200 women attending gynecological OPD with complaints of abnormal uterine bleeding. After obtaining a written informed consent from the participants a detailed history and complete examination including a thorough gynecological examination was performed. A transvaginal ultrasound examination to note for any structural causes for AUB was performed. Thyroid function test (FT3, FT4, TSH) was performed in all study participants and they were then categorized into euthyroid, hypothyroid, hyperthyroid, subclinical hypo or hyperthyroid based on the results. After preliminary preparation all participants were subjected for an endometrial biopsy in the outpatient department and the tissue obtained was sent for histopathological analysis. All the information was tabulated and analyzed using SPSS 22 version with descriptive and inferential statistics (chi square test). A p value of < 0.05 was considered as statistically significant. Results: Heavy menstrual bleeding was the most common menstrual abnormality found in 85% of the study participants.77% had structural causes for AUB whereas 23% had non-structural causes. 79.5% of the patients with AUB were euthyroid whereas 20.5% had some form of thyroid dysfunction. Subclinical hypothyroidism was the most common thyroid dysfunction (15.5%) in this study followed by hypothyroidism (3.5%). Only 1.5% of patients had hyperthyroidism. In the present study no, significant association was found between any particular thyroid dysfunction and specific menstrual pattern or endometrial pattern in histopathology. Conclusions: Testing and treating for thyroid disorder would prove to be cost effective in patients with AUB particularly with nonstructural causes as it would avoid many costly interventions done for AUB.